Help-Seeking Among Pregnant and Postpartum Women With Lifetime Experiences of Opioid Use Disorder and Intimate Partner Violence - Hill, Amber L. (Violence against women, 2024)
We performed content analysis using a qualitative descriptive approach of 15 semistructured interviews with pregnant and postpartum women who have experienced opioid use disorder (OUD) and intimate partner violence (IPV) regarding their experiences seeking help with both issues. Participants described that their partners impacted their ability to seek OUD care; seeking help for OUD and IPV was siloed; they felt more comfortable disclosing OUD than IPV; they perceived pregnancy as a barrier and facilitator to OUD care; and they wished for integrated services. Pregnant and postpartum women experiencing OUD and IPV acknowledged these phenomena intersect and identified a need for more comprehensive services.